Pelaksanaan Kampanye Pemilihan Gubernur Sumatera Barat Berdasarkan PKPU Nomor 13 Tahun 2020 - Devika Putri; Nora Eka Putri (Policy, Law and Political Research Center, 2022)
This study aims to determine the implementation of the West Sumatra Governor Election Campaign based on PKPU Number 13 of 2020. The existence of the Covid-19 pandemic makes the 2020 Campaign Implementation must comply with the health protocols as stipulated in PKPU Number 13 of 2020. The type of research is qualitative research with descriptive methods. Informants were selected using a purposive sampling technique, namely the selection of informants based on certain characteristics according to the research objectives. Data collection is carried out by interviewing related to the problems studied, then documentation studies which are supporting data and relevant to the problems studied in the form of reports, legislation, pictures and other supporting data. The technique of testing the validity of the data uses the triangulation method. While the data analysis technique is done by reducing the data, presenting the data, and drawing conclusions. The results showed that the Implementation of the 2020 West Sumatra Governor Election Campaign had been carried out in accordance with the rules contained in PKPU Number 13 of 2020 although there were still violations committed by the 2020 West Sumatra Governor Candidate Pair. And the factors that influenced the campaign were the campaigners, campaign messages, campaign media, and campaign target audiences